COVID-19 and male fertility: short- and long-term impacts of asymptomatic vs. symptomatic infection on male reproductive potential - Majzoub, Ahmad; Khalafalla, Kareim; Arafa, Mohamed; El Ansari, Walid; Nair, Arun; Al Bishawi, Ahmad; Saleh, Mulham; Khair Ella, Mohamed; ElBardisi, Haitham; Khattab, Muhammad Abu; AlRumaihi, Khalid (Frontiers in Reproductive Health, 2024)
Studies exploring the effect of COVID-19 on male reproductive system suggest a detrimental association, however with conflicting results. The aim of this study was to assess the association between COVID-19 infection and male reproductive potential including hormone profiles and semen parameters.This prospective cohort study included 48 patients with confirmed COVID-19 infection. Patients were subdivided into an asymptomatic group (n=30) and a group with COVID-19 symptoms (n=18). Serum hormone levels including testosterone, LH, FSH and estradiol were collected during active infection (baseline, time 0), and at 3 and 6 months following COVID-19 infection. Semen samples (basic semen analysis and oxidation reduction potential) were collected at 3 and 6 months following infection. Student and paired-t tests were used to compare continuous variables between the study groups and across the studied time intervals, respectively. Multivariate binary logistic regression analysis was performed to explore predictors for COVID-19 symptoms during active infection.Patients with COVID-19 symptoms were significantly older (p=0.02) and had significantly lower serum testosterone levels (p=0.01) and significantly higher LH:Testosterone ratio (p=0.01) than asymptomatic patients. Multivariate analysis revealed older age (OR= 1.18, p=0.03) and lower serum testosterone level (OR=0.8, p=0.03) as independent predictors of symptomatic COVID-19 infection. Significant increase in testosterone (p<0.001 for both) and decrease in LH (p=0.02, p=0.007) and LH:testosterone (p=0.02, p=0.005) levels were observed 3 months and 6 months in patients with COVID-19 symptoms. Asymptomatic patients demonstrated significant increase in testosterone (p=0.02) and decrease in LH:testosterone (p=0.04) levels only at 3 months following COVID-19 infection. No significant differences were observed between the two study groups with regards to the semen analysis results obtained 3 months or 6 months following COVID-19 infection.Significantly lower testosterone values are associated with worse disease severity among men with COVID-19 infection. This association appears to be temporary as a significant increase in testosterone levels are witnessed as early as 3 months following recovery. No significant detrimental effect for COVID-19 infection on testicular sperm production is found in this patient population.